Neonatal outcome of pregnancy with hypertensive disorders in Birat Medical College Teaching Hospital, Morang, Nepal - Jha, Chandra Bhushan; Rimal, Hem Sagar; Yadav, Siddhartha Kumar; Subedi, Ram Bhakta (Journal of Karnali Academy of Health Sciences, 2025)
Background: Hypertensive disorders of pregnancy are multi-organ, heterogeneous disorder of pregnancy and seriously endanger the safety of the mother and the fetus during pregnancy with continuous impact on neonatal period. It causes adverse neonatal outcomes like prematurity, low birth weight (LBW), intrauterine fetal demise (IUFD), intrauterine growth restriction (IUGR), respiratory distress, admission at neonatal intensive care unit (NICU) and neonatal death. The main objective of this study is to assess neonatal outcome in pregnancy with hypertensive disorders.Methods: This was a hospital based cross sectional study carried out in the Department of Paediatrics of Birat Medical College Teaching Hospital, Morang. This study was performed on 175 neonates delivered by pregnant mother with hypertensive disorders who fulfilled the inclusion criteria. Demographic information, detailed clinical and obstetric history, clinical examination, investigations and neonatal outcomes were recorded in the proforma. Data were entered in Microsoft excel and analyzed using SPSS version 16.Results: Among 175 mothers, majority were suffering from gestational hypertension (54.8%) followed by pre-eclampsia (40.6%), with most (60%) being a term pregnancy. Intrauterine growth retardation (IUGR) was 32% and appropriate for gestational age (AGA) were 68%. Perinatal asphyxia comprising of 19% cases was the most common cause of admission. NICU admission was needed in 53.7% neonates for various complications with neonatal mortality seen in 6% cases.Conclusion: Hypertensive disorders of pregnancy is associated with the increased risk of adverse neonatal outcome.